(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objective: Diagnosing and treating ovarian endometrioma at the clinical stage and making a comparative study of the treatment results. Methods: In 2018-2019, 63 women aged 20-45 years diagnosed with ovarian endometriosis in the gynecology department of the Obstetrics and Gynecology Hospital of the National Center for Maternal and Child Health were included in the study. A hospital-based clinical prospective case-control study was used. Results: The first group of women received dienogest after surgery for 3 months during which pain during menstruation (p < 0.001), pain during intercourse (p < 0.001), and chronic pelvic pain (p < 0.016) was assessed. The second group of women received dienogest before surgery for 3 months during which pain during menstruation (p < 0.001), pain during intercourse (p < 0.001), and chronic pelvic pain (p < 0.001) was assessed. In this comparative surgical study, in the first group 14 (43.8) had trouble having the endometrioma removed, and in the second group, 23 (74.2%) had no trouble having the endometrioma removed. Conclusion: The use of synthetic progestin before surgical removal of moderate to severe endometriosis with laparoscopy decreases the blood loss during surgery (p < 0.021) and facilitate the removal of the endometrium from the ovary